Parallel unbalanced three-phase power flow analysis including distributed generation models - Syafii, 1974-; Khalid Mohamed Nor; Fakulti Kejuruteraan Elektrik (2011)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2011